Development of Biology Teaching Materials Based on Karawang Local Potential to Improve Environmental Literacy and Problem-Solving Skills of Junior High School Students - Devi, Cindy Rantika; Sriyati, Siti; Hamdiyati, Yanti (Jurnal Paedagogy, 2025)
This study aims to develop biology teaching materials based on the local potential of rice farming in Karawang district to enhance students’ environmental literacy and problem-solving skills. This study employed a research and development model using the ADDIE framework. The research was conducted in a junior high school in Karawang with a total sample of 70 students, consisting of 35 students in the experimental class and 35 students in the control class. The instruments used in this study included teaching materials based on local agricultural potential in Karawang, environmental literacy tests, and problem-solving assessments. T-test validation analysis and N-gain calculation were used to evaluate the effectiveness of the teaching materials. The results showed that the average environmental literacy score of the experimental class was higher than that of the control class, and the problem-solving ability results also indicated that the average score of the experimental class was higher than that of the control class. These findings suggest that the developed local potential-based teaching materials can effectively improve the environmental literacy and problem-solving skills of junior high school students.